Evaluation of Community Pharmacists’ Attitude and its Association with their Practice toward Dengue Prevention - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Aims: The study aimed to evaluate community pharmacists’ (CPs) attitude and its association with their practice toward dengue prevention. Materials and Methods: A cross-sectional study was done using a pre-validated and self-administered questionnaire developed after an intensive and relevant literature review. The convenience sampling method was used during the study period. Registered CPs were approached to achieve the sample size of 205 respondents. For data analysis, descriptive and inferential statistics were used using Statistical Package for the Social Sciences version 25.0. P < 0.05 was considered statistically significant. Results: Of 205 respondents, 15 (7.3%) of them strongly agreed and 129 (62.9%) moderately-agreed that they could play an important role in preventing dengue infection. Whereas, the majority of the respondents, 92 (44.9%) were neutral when asked whether they felt comfortable in handling dengue patients. The majority of the respondents (n = 172, 83.9%) had a positive attitude toward dengue infection. Conclusion: The respondents had a positive attitude toward dengue. There was no statistically significant association between their attitude and practices toward dengue prevention observed.